Critical Need for Health Literacy and Policy Reforms for Reduction of Self-Medication in Pakistan - Alvi, Um-e-Habiba (International Journal of Pathology, 2023)
Dear Editor,The terminology self-medication (SM) refers to "utilization of medications treatment of self-diagnosed afflictions, symptoms or the periodic / persistent use of a prescription meds for chronic disease or symptoms". 1 It may involve the use of over-the-counter (OTC), prescription-only-meds (POM), or supportive and alternative meds (SAM) without first consulting a medical doctor. SM ways include repeating a previous physician prescription, ingesting unused drugs, employing home-based supplements and cures on the advice of relatives/friends or colleagues. 2 SM is a risky endeavor that leads to erroneous diagnoses, poor meds selection, dependence, abuse issues, and waste of healthcare resources. SM is a significant global problem that affects both wealthy and developing nations.1, 2 As per the findings, the prevalence rate of SM ranges from 32.5 percent to 81.5 percent worldwide.The prevalence of SM and its continued impact on public health make it an important topic of discussion in Pakistan. Recent studies suggest that between 53% and 61.3% of Pakistan's population is affected by SM.3 93% of participants reported using SM to take analgesics, and 69% reported using SM to take antipyretics, and 52% used SM to take antibiotics .2,3 Additionally, the Pakistani population was found to make use of SAM and home-based treatments.4 A recent survey revealed that, on average in Pakistan, each community pharmacy there serves 5.5 people per day, of whom 7.9 receive drugs without a prescription.5 Increasing percentage of SM in Pakistan, may be attributable to a combination of reasons, including ready availability of medications, inadequate health education, and widespread drug advertising.3-5 Misdiagnosis, improper treatment, and additional health problems are all possible outcomes of SM approaches based on individual practitioners' prior experience with the same ailment.1 SM involvement is associated with polypharmacy, unwanted side effects, medication interactions, resistance development, and a heavier cost burden.6